Estimation Model for Effective Thermal Conductivity of Reinforced Concrete Containing Multiple Round Rebars - Hyung Gyun Noh; Hie Chan Kang; Moo Hwan Kim; Hyun Sun Park (International Journal of Concrete Structures and Materials, 2018)
Abstract The objective of this research is to estimate the effective thermal conductivity model for the reinforced concrete containing round rebars. The thermal network concept and Fourier’s law are used to develop a mathematical model to calculate the effective thermal conductivity (k eff) of reinforced concrete with different numbers of round rebars oriented either normal or parallel to the heat-transfer direction, and different volume fractions of steel. Model predictions generally agree well with results of numerical simulations using the finite-volume method (FVM). FVM results suggest that at fixed volume fractions of steel, the effective thermal conductivity decreases as the number of round rebars increases if the rebars are in the normal orientation but increases as the number of round rebars increases if they are in the parallel orientation. This research can be used in practical conditions to predict the effective thermal conductivity of reinforced concrete containing round rebars accurately.